A new fish species of the walking snakehead group, the genus Channa (Channidae, Perciformes) in Vietnam - Hao, Nguyen Vam; Hanh Tien, Nguyen Thi; Dieu Phuong, Nguyen Thi (Academia Journal of Biology, 2012)
Channa longistomata sp. n. (Figs. 1, 2) Samples: 12 fish samples, L = 92-156 mm, Lo = 82-132 mm. Holotype: Sample code H.Na 011.04.001. L = 153 mm; Lo = 124 mm, collected at Tam Chuc lake, Ba Sao town, Kim Bang district, Ha Nam province, dated 21/04/2011. Paratypes: 5 samples, sample code H. Na.011.04.002. L = 132 mm. Lo = 106 mm, collected at Tam Chuc lake, Ba Sao town, Kim Bang district, Ha Nam province, dated 21/042011. Sample code H.B.65.11.011 L = 152 mm, Lo = 125 mm; H.B.65.11.012, L = 156 mm, Lo = 132 mm; H.B.65.11.013, L = 144 mm, Lo = 123 mm và H.B.65.11.014, L = 130 mm, Lo = 110 mm collected at Thac Bo, Da Bac district, Hoa Binh province, dated 20/11/1965. Samples preseved at Fish Museum of Research Institute for Aquaculture No.I, Bac Ninh. Diagnosis: Mouth arched, depth and narrow, mouth length wider than mouth width. Incision of lip along and little over the margin of eye equal eyes diameters origin. The dorsal fin origin in front of pelvic fin origin. The distant from pelvic fin origin to annal fin equal to meeting point of 2 gill arches. Especially toungue flat, thin and it has waist of middle toungue and small round proglossis. Description: Body length, the cylinder from the back side up gradually of high body close to the body thickness. The depth of caudal peduncle is short and height. The head is relative flat. Short snout. Round eyes located on the half first part of the head. Distances between 2 eyes were wide and relative flat. Mouth arched depth and narrow, mouth length wider than mouth width. Tougue flat thin and it has waist of middle toungue and small round of proglossis. (figs. 2a, b, c, d). Fins: D = 33 – 35; A = 22 -23; P = 14 – 15; V = 1,4 -5; C = 12; Scales: 42[...]46, scales around caudal peduncle =18, Lo = 5,48H = 3,8T T = 4,63Ot = 7,18O = 3,07 OO. OO = 2,33 O. H = 1,58 h. Fins of dorsal and anal are long. Dorsal fin origin in front of pelvic fin origin. The distant from pelvic fin origin to anal fin origin equal its to the start meeing point of 2 gill archs. Caudal fin shaped round of ending. All fins are soft. Head and body covered by scale. Lateral line discontinues which interrupted at the middle. Coloration: Color of body gray, no bar. Dorsal fin, annal fin and caudal fin have its outer of red-pink or spark yellow (white when preserved). Pectoral fins have from 3 to 5 black bars. Remarks: C. longistomata sp. n. distinguished from other species of C. gachua (Hamilton) and C.orientalis Bloch & Schneider by the combination of the following characters: mouth arched depth and narrow. The mouth length is bigger than the mouth width. The incision lip along reaching after the margin of eye which equals the eye diameter. Dorsal fin origin in front of pelvic fin origin. Toungue flat and its middle waist narrow, small round of proglossis. Two species C. gachua (Hamilton) and C. orientalis Bloch & Schneider have mouth arched shallow and wide, mouth length smaller than mouth width. The incision lip along reaching middle of eye or a little over margin of eye. Dorsal fin origin after or opposite of pelvic fin origin. Toungue flat and no waist, triangle long, small pointed of proglossis (C. gachua) or flat round of proglossis (C. orientalis). Distribution: Provinces of Da river basin (Dien Bien, Lai Chau, Son La and Hoa Binh) and distribution in lakes near regions of lime mountains of Ha Nam and Ninh Binh. Etymology: Channa longistomata was named according to specific characteristics with a long mouth which is different with the other similar species.